Moderation of pathogen-induced mortality: the role of density in Bacillus thuringiensis virulence. - Raymond, B; Ellis, R; Bonsall, M (2009)
Virulence in pathogens may be increased or decreased in order to maximize reproduction and transmission. We investigated how reproduction and virulence in the entomopathogen Bacillus thuringiensis (Bt) changed with bacterial density. We predicted that virulence would be moderated at high pathogen densities because extended time to death allows more growth in hosts. We found that pathogen reproduction (spores produced per cadaver) peaked at an intermediate time to death and was lowest in hosts that die early. Manipulating spore density (spores per unit area of leaf) by combining pathogenic Bt spores with a non-pathogenic mutant confirmed our prediction: larval 5-day mortality was reduced at higher pathogen densities. Pathogen reproduction increased with the density of pathogenic Bt. We hypothesize that more effective reproduction at high density is a consequence rather than a cause of density-dependent virulence.